A COUPLED NONLINEAR BUCKLING AND PROGRESSIVE DAMAGE MODEL FOR COMPOSITE SHELL STRUCTURES - Юніс, Башир; Мірошников, Віталій (SWorldJournal, 2026)
Thin-walled composite shells fabricated from carbon fiber–reinforced polymer (CFRP) and glass fiber–reinforced polymer (GFRP) are widely employed in aerospace structures due to their high specific stiffness and strength. Their structural response under co